Analisis Proses Abstraksi Matematika dalam Memahami Konsep dan Prinsip Geometri Ditinjau dari Teori Van Hiele - As Elly S; Novianti Mandasari (Jurnal Pendidikan Matematika:Judika Education, 2018)
This study aims to analyze the process of abstraction of students of class XI IPA 2 of SMA Negeri 6 Lubuklinggau in understanding the concepts and principles of geometry in terms of Van Hiele's theory. The method used in research is a qualitative method. Data were analyzed through three stages, namely the stage of data preduction, data presentation and conclusion drawing. The results of data analysis obtained from the five steps of thinking based on Van Hiele's theory that the thinking of students of class XI IPA 2 of SMA Negeri 6 Lubuklinggau is only at stage 0 to stage 2, whereas for stage 3 and stage 4 the level of thinking of class XI IPA 2 students Lubuklinggau still has difficulty in drawing conclusions from things that are general to things that are specific and at this stage is also a stage of thinking that is high, complicated and complex. Conclusion, the level of thinking of students of XI Science 2 of SMA Negeri 6 Lubuklinggau is still low in understanding the concepts and principles of geometry in terms of van hiele's theory. Keywords: Geometry Concept, Keori Van Hiele, Abstraction Process